The risk of vancomycin toxicity in patients with liver impairment - Luigi Brunetti; Jong Hwa Song; David Suh; Heui Jae Kim; Yeon Hee Seong; Dae Song Lee; Seung-Mi Lee; Dong-Churl Suh (BMC, 2020)
Abstract Background The influence of liver disease on the pharmacokinetic profile, the risk of acute kidney injury, and excessive drug exposure in patients treated with vancomycin was examined. Methods A retrospective cohort study was performed with patients discharged from a medical center between January 2011 and June 2018 who received vancomycin therapy. Patients were stratified according to liver dysfunction (no to mild liver dysfunction (NMLD) and moderate to severe liver dysfunction (MSLD) based on the Child-Pugh score. The risk of acute kidney injury was compared between patients who were stratified by the attainment of a target serum trough concentration (10 mg/dL to 20 mg/dL) and the vancomycin ratio formed between the area under the curve and minimum inhibitory concentration. The impact of liver dysfunction and a daily dose of vancomycin on the risk of acute kidney injury and vancomycin AUC:MIC > 600 were tested using logistic regression with and without adjusting for the study variables. Results A total of 408 patients empirically treated with vancomycin were included in this study (237 with NMLD and 171 with MSLD). Mean vancomycin trough concentrations (17.5 ± 8.4 mg/dL versus 15.3 ± 5.2 mg/dL, p = 0.0049) and AUC:MIC ratios (549.4 ± 217.2 versus 497.5 ± 117.3, 0.0065) were significantly higher in the MSLD group when compared to the NMLD group, respectively. Vancomycin clearance was also lower in the MSLD group and corresponded to a longer half-life. The proportion of patients who developed acute kidney injury was greater in patients with MSLD when compared to NMLD (7.6% versus 3.8%, respectively; p = 0.0932); however, the difference was statistically insignificant. Furthermore, supratherapeutic serum trough concentrations and AUC:MIC ratios were more common in the MSLD group versus the NMLD group (27.5% versus 13.9%, p = 0.0007 and 28.7% versus 17.3%, respectively; p = 0.0063). Conclusions MSLD correlates with an increased risk of supratherapeutic vancomycin exposure. Although patients with MSLD had a higher risk of acute kidney injury, the difference was not significant.